IMPROVING ENGLISH VOCABULARY THROUGH PEER LEARNING ACTIVITIES - Azzahra, Fatimah; Muliati, A.; Aeni, Nur (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This quantitative study aims to explore the effectiveness of peer learning activities in improving students’ English vocabulary. The research employed a pre-experimental design involving one group pretest-posttest, with participants consisting of 25 eighth-grade students at SMP Negeri 1 Parangloe. Data were collected through vocabulary tests administered before and after the peer learning intervention. The findings indicate a notable improvement in students’ vocabulary mastery. Pretest results showed that 68% of students were in the "Poor" category, with no students achieving "Good" or "Very Good" scores. After the intervention, 40% of students reached the "Good" and "Very Good" categories, while those in the "Poor" range dropped to 32%. The mean score increased from 63.20 to 77.40, with consistent standard deviation and low standard error, indicating reliable results. The N-Gain score of 0.38 classified the vocabulary improvement as "Average." Furthermore, the paired sample t-test yielded a Sig. (2-tailed) value of 0.000, which is lower than 0.05, leading to the rejection of the null hypothesis (H₀) and acceptance of the alternative hypothesis (H₁). In conclusion, peer learning activities have a statistically significant and positive effect on enhancing students’ English vocabulary skills, although some students may still require additional support for further improvement.